PELATIHAN PEMASANGAN JARINGAN INSTALASI LISTRIK 3 PHASA UNTUK PENGOPERASIAN MOTOR INDUKSI 3 PHASA BAGI SISWA-SISWI SMK NEGERI 2 KARANGANYAR - maju binoto; Fariyono (Abdi Masya, 2026)
There are two types of alternating current electrical installation networks: single-phase and three-phase. Three-phase electrical networks are used to operate three-phase induction motors. To operate a three-phase induction motor, a proper three-phase electrical installation is required. The installation and connection of three-phase electrical installations must comply with PUIL regulations to prevent short circuits. This was the first time the training participants at SMK Negeri 2 Karanganyar received training on properly installing and connecting three-phase electrical installations. The students had never previously received lessons on installing and connecting three-phase installations. Therefore, the Community Service Team of the D3 Electrical Engineering Study Program at STT "Warga" Surakarta conducted a Community Service activity in the form of training for SMK Negeri 2 Karanganyar students. The purpose of this training was to provide knowledge and technology on how to install and connect 3-phase electrical installations to properly operate 3-phase induction motors. The workshop for students of SMK Negeri 2 Karanganyar was held over two days, from August 27th to 28th, at the Electrical Circuits Laboratory of the D3 Electrical Engineering Study Program at STTW Surakarta. The method used was material presentation and training on installing and connecting 3-phase electrical installations to properly operate 3-phase induction motors. The training left the students very enthusiastic and eager to provide further training to their fellow students in the future.